The Influence of Government Support, Digital Literacy, and Market Orientation on Agrotourism Sustainability in the Menoreh Mountains - Hermawan; Dara Salsabila Rianti; Anjar Dwi Astono (Proceedings of the International Conference on Entrepreneurship (IConEnt), 2025)
This study aims to analyze the influence of government support, digital literacy, and market orientation on agrotourism sustainability in the Menoreh Mountains. A quantitative approach with explanatory design was employed, involving 100 respondents consisting of agrotourism managers and operators. Data were collected through Likert-scale questionnaires and analyzed using multiple linear regression. The results reveal that government support has a significant positive impact on agrotourism sustainability through policies, infrastructure provision, and destination promotion. Digital literacy significantly enhances competitiveness via social media utilization, tourism applications, and online information management. Market orientation also shows significant effects by driving product adaptation, service adjustments, and targeted promotional strategies. Simultaneously, the three independent variables contribute significantly to agrotourism sustainability in the Menoreh Mountains. These findings indicate that synergy among policy support, digital capabilities, and adaptive marketing strategies is the key to strengthening competitiveness and ensuring long-term community-based agrotourism sustainability.